Analysis of Factors Affecting the Seismic Performance of Widened Flange Connections in Mid-Flange H-Beams and Box Columns - Tigist Demssice Gemechu; Linfeng Lu (Buildings)
Following the Northridge and Kobe earthquakes, research has increasingly focused on achieving high ductility in beam-to-column connections. This study investigates the seismic performance of connections featuring widened beam-end flanges in mid-flange H-beams and box columns, an area with limited prior research compared to I-section columns and narrow-flange H-beams. Detailed finite element modeling using ABAQUS 6.1.4 demonstrates that widened beam-end flanges significantly improve bending capacity and ductility by relocating the plastic hinge away from the connection, thereby enhancing seismic resilience. Key findings include the identification of optimal design parameters: flange length ranging from 0.55 to 0.75 times the beam flange width, beam flange cutting length between 0.36 and 0.39 times the beam depth, and flange cutting depth from 0.19 to 0.23 times the beam flange width. These parameters ensure effective plastic hinge development and improved structural performance. This study introduces a novel approach that emphasizes geometric optimization over material-based enhancements, offering a cost-effective and practical solution for improving seismic performance and extending previous research insights.